PERHITUNGAN STRUKTUR ATAS JEMBATAN KOMPOSIT SUNGAI KARANG MUMUS JALAN PERNIAGAAN KOTA SAMARINDA CALCULATION OF COMPOSITE STRUCTURES BRIDGE RIVER KARANG MUMUS SAMARINDA CITY - WINATA TAMPUBOLON, ROLANDO (KURVA S JURNAL MAHASISWA, 2013)
Bridge as a means of transport has a very important role for the movement of traffic and boost the population and economy of a region Seeing the importance of the function of a bridge.the bridge must meet the requirements of making the existing bridge.One of the requirements that must be met in the manufacture of the bridge is the bridge resistance of the load bearing that works well which is caused by humans or vehicles passing over the bridge . there are many things that must be considered in the calculation of the factors which must be considered include , bridge dead load , live load , wind load , temperature loads and loads of vehicles or trafficSkripisi. Long span composite bridge being simulated is 20 m, width 6 m carriageway, pavement width of 0.5 m and 0.5 m right side of the left side, so that the total width of the bridge 7 m. the size of the railing is 15 cm x 15 cm, and used composite type girder type I-beams